The Cost and Quality of Life of Malaysian Type 2 Diabetes Mellitus Patients with Chronic Kidney Disease and Anemia - Azmi S.; Goh A.; Muhammad N.A.; Tohid H.; Rashid M.R.A. (Elsevier Inc., 2024)
Indexed by SCOPUS/ERA